Pengaruh Self-Efficacy Terhadap Academic Burnout Siswa Kelas XI di SMA Negeri 1 Dramaga (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the levels of academic burnout and self-efficacy, as well as to examine the influence of self-efficacy on academic burnout among Grade XI students in the health stream at SMA Negeri 1 Dramaga. The study employs a quantitative approach using a causal-associative method. The research population consisted of 108 students, all of whom were included in the sample via a saturated sampling technique. Data were collected using a modified Maslach Burnout Inventory–Student Survey (MBI-SS) to measure academic burnout and the General Self-Efficacy Scale (GSE) to measure self-efficacy; both instruments underwent validity and reliability testing. Data were analyzed using descriptive statistics and simple linear regression with the aid of IBM SPSS Statistics 26.0. The results indicate that the majority of students experienced academic burnout in the moderate category (80.6%), while self-efficacy levels fell into the moderate (50.9%) and high (49.1%) categories. Hypothesis testing revealed that self-efficacy has a significant negative effect on academic burnout (t = −8.057; p < 0.001). An R² value of 0.380 indicates that self-efficacy contributes 38% to the variance, while the remaining 62% is influenced by factors outside the model.